Minimally invasive needle tenotomy vs. platelet rich plasma injection in the treatment of chronic elbow epicondylitis - Chantal T. Nguyen, MD; Michelle H. Lee, MD; Matthew W. Kaufman, MD; Yue Meng, MD; Jyotsna A. Koduri, MD; Geoffrey Abrams, MD; Emilie V. Cheung, MD; Michael T. Freehill, MD; Eugene Y. Roh, MD (JSES International)
Background: Medial and lateral epicondylitis, characterized by repetitive microtraumas to common flexor and extensor tendons, respectively, are common causes of elbow pain in adults. Though symptoms are generally self-limiting, 10% of cases are refractory to conservative management, persisting for greater than 18 months, and leading to surgery, which can have increased risk of complications. There is minimal data on sustained pain relief and functional benefit for newer nonsurgical management options, such as minimally invasive needle tenotomy (MINT), and platelet-rich plasma (PRP) for chronic elbow epicondylitis. Additionally, no previously established correlation exists between magnetic resonance imaging (MRI) severity of chronic epicondylitis with pain and functional improvement in MINT- and PRP-treated patients. Methods: A retrospective review of 51 adults (n = 23 for MINT; n = 28 for PRP) was conducted to investigate long-term outcomes in pain relief (via visual analog scale or VAS) and improvements in upper extremity function (via quick disability of the arm, shoulder, and hand questionnaire or qDASH). These outcomes were correlated with radiographic evidence of epicondylitis severity, assessed by the grade of epicondylitis and percentage thickness of tendon tears. Results: There were significant improvements in pain (VAS), but no significant differences in function (qDASH) following MINT and PRP. On average, VAS score improved by 2.6 (P < .001) post-MINT and by 3.8 (P < .001) post-PRP combined for all follow-up time points. No adverse events were reported over the entire study. A significantly higher percentage of patient-reported pain relief was noted post-MINT at all follow-up time points. VAS and qDASH outcomes post-MINT and post-PRP were not correlated with the initial MRI severity of epicondylitis. Conclusions: There are multifactorial benefits of both MINT and PRP as safe, nonopen surgical modalities that can be used, despite MRI severity, to provide sustained pain relief for patients with refractory elbow epicondylitis.